Teaching History in High School: an inside look at the classroom - Valtuille, Florencia (Universidad Nacional del Litoral, 2022)
How are teaching practices of History education in high school formed? What are the existing differences and distortions between the curricular prescriptions and the pedagogical practices in schools? This article reassumes the research work of my master’s degree dissertation and considers some of the conditioning nuances of History education in the current setting of high school. In an attempt to approach the real curriculum in schools, some records of classroom observations and testimonies of teachers are included, who express their approaches, strategies, obstacles and concerns regarding the criteria for teaching this school subject. In addition, the purposes and activities stated, suggested and practised daily in the classroom are analysed. To conclude, vacancy areas and the strength of certain teaching practices which should be addressed by the production of didactic knowledge are pointed out.